Analyzing the prohibition of prostitution through the lens of Maqasid al-Shari'ah focuses on upholding Al-Daruriyyat Al-Khamsah: Analisis terhadap larangan prostitusi melalui kacamata Maqasid al-Syari’ah berfokus pada pemenuhan Al-Daruriyyat Al-Khamsah - Adrianto; Haslinda (QISTHOSIA : Jurnal Syariah dan Hukum, 2026)
Prostitution destroys the institution of valid marriage and obscures the clarity of lineage due to promiscuity/free sex. This practice is highly vulnerable to triggering sexual violence, human exploitation, and the spread of infectious diseases. Prostitution localization is often closely related to the circulation of liquor and illicit drugs. All forms of commercial sexual transactions constitute a form of disobedience to God's law that degrades the spiritual morals of the perpetrators. And prostitution transactions constitute a waste and the acquisition of illicit wealth. The primary goal of prohibiting prostitution through the Maqasid al-Shari'ah approach is to realize public welfare (maslahah) and prevent harm/corruption (mafsadah). By focusing on universal protection (Al-Daruriyyat Al-Khamsah - the five essential needs), this prohibition is designed to safeguard the core foundations of human life from moral and social destruction. research of an Approach of the Higher Objectives/Purposes of Islamic Law of prostitution by Using a normative legal approach with an Approach of the Higher Objectives/Purposes of Islamic Law research, research results show that First The approach of the Higher Objectives/Purposes of Islamic Law (Maqāṣid al-Sharīʿah) to prostitution is that it is strictly forbidden (haram) because it violates the fundamental, essential human needs (al-darūriyyāt al-khamsah) that Sharia aims to protect. Second, the approach of the Higher Objectives/Purposes of Islamic Law (Maqāṣid al-Sharīʿah) regarding prostitution results in a strict prohibition, framing it as a major violation of the foundational goals of Islamic jurisprudence, primarily the protection of religion, honor, lineage, and life.